Phylogenetically and spatially close marine sponges harbour divergent bacterial communities - Hardoim, C. C. P. (2012)
Recent studies have unravelled the diversity of sponge-associated bacteria that may play essential roles in sponge health and metabolism. Nevertheless, our understanding of this microbiota remains limited to a few host species found in restricted geographical localities, and the extent to which the sponge host determines the composition of its own microbiome remains a matter of debate. We address bacterial abundance and diversity of two temperate marine sponges belonging to the Irciniidae family - Sarcotragus spinosulus and Ircinia variabilis – in the Northeast Atlantic. Epifluorescence microscopy revealed that S. spinosulus hosted significantly more prokaryotic cells than I. variabilis and that prokaryotic abundance in both species was about 4 orders of magnitude higher than in seawater. Polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE) profiles of S. spinosulus and I. variabilis differed markedly from each other – with higher number of ribotypes observed in S. spinosulus – and from those of seawater. Four PCR-DGGE bands, two specific to S. spinosulus, one specific to I. variabilis, and one present in both sponge species, affiliated with an uncultured sponge-specific phylogenetic cluster in the order Acidimicrobiales (Actinobacteria). Two PCR-DGGE bands present exclusively in S. spinosulus fingerprints affiliated with one sponge-specific phylogenetic cluster in the phylum Chloroflexi and with sponge-derived sequences in the order Chromatiales (Gammaproteobacteria), respectively. One Alphaproteobacteria band specific to S. spinosulus was placed in an uncultured sponge-specific phylogenetic cluster with a close relationship to the genus Rhodovulum. Our results confirm the hypothesized host-specific composition of bacterial communities between phylogenetically and spatially close sponge species in the Irciniidae family, with S. spinosulus displaying higher bacterial community diversity and distinctiveness than I. variabilis. These findings suggest a pivotal host-driven effect on the shape of the marine sponge microbiome, bearing implications to our current understanding of the distribution of microbial genetic resources in the marine realm.